Solid Suspension by an Upflow Mixture of Fluid and Larger Particles. (24th July 2013) - Di Felice, Renzo; Rotondi, Marco
Abstract : In this paper new experimental observation is reported in order to shed light on the fluid dynamic interactions between the solid and the fluid phases in binary solid mixture suspensions. More specifically the case where a solid particle species is suspended by a slurry made up of fluid and larger particles has been investigated as there appear to be no previous studies on this type of systems. The effect of the presence of the larger solids in the fluidising media is quite evident from the experimental observation, and this effect can be quantified in first approximation by a very simple model based on the assumption that the larger solid restricts the available area for the fluid flow.